Diagnosis lesi serviks dengan sitologi Pap’s Smear menggunakan teknik konvensional - Kartika, Ika; Dewi, Citra; Desmaradd, Soraya Sagita; Fitria, Zahra; Sandria, Sandria (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Cervical cancer is one of the highest malignancies globally and is the second leading cause of death in women in Indonesia. Pap Smear cytology detects precancerous lesions as precursor lesions and is indicated for all married women regularly. The discovery of precancerous lesions must prompt immediate treatment to prevent the progression to cervical cancer. We facilitated counseling and Pap Smear examination. This program aimed to raise public awareness and knowledge regarding the importance of early detection of cervical cancer and cervical precancerous lesions. Counseling and examination activities were held on Saturday, 15th October 2022, at AR.Bunda Hospital, Prabumulih, South Sumatera. This community service has involved 46 participants. The majority of Pap Smear results were non-specific chronic cervicitis, classified as Negative for Intraepithelial Lesion or Malignancy (NILM). Prevention of cervical cancer may be conducted through counseling and early detection.